2002
DOI: 10.1046/j.1365-8711.2002.05599.x
|View full text |Cite
|
Sign up to set email alerts
|

The physical properties of the Lyα forest at

Abstract: Combining a new, increased data set of eight quasi‐stellar objects (QSOs) covering the Lyα forest at redshifts 1.5 < z < 3.6 from VLT/UVES observations with previously published results, we have investigated the properties of the Lyα forest at 1.5 < z <4. With the six QSOs covering the Lyα forest at 1.5 < z < 2.5, we have extended previous studies in this redshift range. In particular, we have concentrated on the evolution of the line number density and the clustering of the Lyα forest at z≤ 2.5, where the Lyα… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
284
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(318 citation statements)
references
References 42 publications
27
284
7
Order By: Relevance
“…The result from the HST/FOS Quasar Absorption Line Key project shows such a slow change in the dn/dz evolution at z < 1.5 (Weymann et al 1998), compared to a much steeper dn/dz evolution shown at z > 2 ( Kim et al 1997Kim et al , 2001Kim et al , 2002. Cosmic variance also seems to increase at lower z .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The result from the HST/FOS Quasar Absorption Line Key project shows such a slow change in the dn/dz evolution at z < 1.5 (Weymann et al 1998), compared to a much steeper dn/dz evolution shown at z > 2 ( Kim et al 1997Kim et al , 2001Kim et al , 2002. Cosmic variance also seems to increase at lower z .…”
Section: Introductionmentioning
confidence: 91%
“…Note that the redshift based on the emission lines is known to be underestimated compared to the one measured from other quasar emission lines such as C iv (Tytler & Fan 1992;Vanden Berk et al 2001). The spectrum of Q1101−264 is the same one as analysed in Kim et al (2002), while the rest of spectra are from Kim et al (2007). The raw spectra were obtained from the ESO VLT/UVES archive and were reduced with the UVES pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Some spectral regions and results for HE 1122À1648 are described by Kim et al (2002). The spectral range covered by the analysis is from 3050 Å to the C iv emission line in both cases.…”
Section: Observations and Absorption Line Fitsmentioning
confidence: 99%
“…The continuum was initially determined as described by Kim et al (2002), and the absorption lines were fitted by multiple Voigt profiles, using the VPFIT program described by Webb (1987;Rauch et al 1992) as updated by R. F. Carswell et al 5 The whole of the available spectrum was fitted so as to provide a self-consistent set of line profile parameters for each ion. Except where noted otherwise below, different ions with components in the same system were not constrained to have the same redshift, and their Doppler parameters were fitted independently.…”
Section: Observations and Absorption Line Fitsmentioning
confidence: 99%
“…The statistical and physical properties of Ly-α (e.g. [13,21]) and C IV (e.g. [22]) absorbers were refined and assessed.…”
Section: The Igm Probed By Single Lines Of Sightmentioning
confidence: 99%